Natural history of multiple sulfatase deficiency: Retrospective phenotyping and functional variant analysis to characterize an ultra‐rare disease - Adang, Laura A. (J Inherit Metab Dis, 2020)
Multiple sulfatase deficiency (MSD) is an ultra‐rare neurodegenerative disorder caused by pathogenic variants in SUMF1. This gene encodes formylglycine‐generating enzyme (FGE), a protein required for sulfatase activation. The clinical course of MSD results from additive effect of each sulfatase deficiency, including metachromatic leukodystrophy (MLD), several mucopolysaccharidoses (MPS II, IIIA, IIID, IIIE, IVA, VI), chondrodysplasia punctata, and X‐linked ichthyosis. While it is known that affected individuals demonstrate a complex and severe phenotype, the genotype‐phenotype relationship and detailed clinical course is unknown. We report on 35 cases enrolled in our retrospective natural history study, n = 32 with detailed histories. Neurologic function was longitudinally assessed with retrospective scales. Biochemical and computational modeling of novel SUMF1 variants was performed. Genotypes were classified based on predicted functional change, and each individual was assigned a genotype severity score. The median age at symptom onset was 0.25 years; median age at diagnosis was 2.7 years; and median age at death was 13 years. All individuals demonstrated developmental delay, and only a subset of individuals attained ambulation and verbal communication. All subjects experienced an accumulating systemic symptom burden. Earlier age at symptom onset and severe variant pathogenicity correlated with poor neurologic outcomes. Using retrospective deep phenotyping and detailed variant analysis, we defined the natural history of MSD. We found that attenuated cases can be distinguished from severe cases by age of onset, attainment of ambulation, and genotype. Results from this study can help inform prognosis and facilitate future study design.